Aortic-brachial stiffness mismatch and mortality in dialysis population - Fortier, Catherine; Mac-Way, Fabrice; Desmeules, Simon; Marquis, Karine; De Serres, Sacha A; Lebel, Marcel; Boutouyrie, Pierre; Agharazii, Mohsen (Hypertension (Dallas, Tex. 1979), 2015)
We hypothesized that increased aortic stiffness (central elastic artery) combined with a decrease in brachial stiffness (peripheral muscular artery) leads to the reversal of the physiological stiffness gradient (ie, mismatch), promoting end-organ damages through increased forward pressure wave transmission into the microcirculation. We, therefore, examined the effect of aortic-brachial stiffness mismatch on mortality in patients in need of dialysis. In a prospective observational study, aortic-brachial arterial stiffness mismatch (pulse wave velocity ratio) was assessed using carotid-femoral pulse wave velocity divided by carotid-radial pulse wave velocity in 310 adult patients on dialysis. After a median follow-up of 29 months, 146 (47%) deaths occurred. The hazard ratio (HR) for mortality related to PWV ratio in a Cox regression analysis was 1.43 (95% confidence interval [CI], 1.24-1.64; P<0.001 per 1 SD) and was still significant after adjustments for confounding factors, such as age, dialysis vintage, sex, cardiovascular disease, diabetes mellitus, smoking status, and weight (HR, 1.23; 95% CI: 1.02-1.49). The HRs for changes in 1 SD of augmentation index (HR, 1.35; 95% CI, 1.12-1.63), carotid-femoral pulse wave velocity (HR, 1.29; 95% CI, 1.11-1.50), and carotid-radial pulse wave velocity (HR, 0.80; 95% CI, 0.67-0.95) were statistically significant in univariate analysis, but were no longer statistically significant after adjustment for age. In conclusion, aortic-brachial arterial stiffness mismatch was strongly and independently associated with increased mortality in this dialysis population. Further studies are required to confirm these finding in lower-risk groups.